Ultraviolet spectroscopy of the blue supergiant SBW1: the remarkably weak wind of a SN 1987A analogue. Issue 2 (17th March 2017) - Smith, Nathan; Groh, Jose H.; France, Kevin; McCray, Richard
Abstract: The Galactic blue supergiant SBW1 with its circumstellar ring nebula represents the best known analogue of the progenitor of SN 1987A. High-resolution imaging has shown Hα and infrared structures arising in an ionized flow that partly fills the ring's interior. To constrain the influence of the stellar wind on this structure, we obtained an ultraviolet (UV) spectrum of the central star of SBW1 with the Hubble Space Telescope Cosmic Origins Spectrograph. The UV spectrum shows none of the typical wind signatures, indicating a very low mass-loss rate. Radiative transfer models suggest an extremely low rate below 10 −10 M⊙ yr −1, although we find that cooling time-scales probably become comparable to (or longer than) the flow time below 10 −8 M⊙ yr −1 . We therefore adopt this latter value as a conservative upper limit. For the central star, the model yields T eff = 21 000 ± 1000 K, log( g eff ) = 3.0, L ≃ 5 × 10 4 L⊙, and roughly Solar composition except for enhanced N abundance. SBW1's very low mass-loss rate may hinder the wind's ability to shape its nebula and to shed angular momentum. The spin-down time-scale for magnetic breaking is more than 500 times longer than the age of the ring. This, combined with the star's slow rotation rate, constrains merger scenarios to form ring nebulae. The mass-loss rate is at least 10 times lower than expected from mass-loss recipes, without any account of clumping. The physical explanation for why SBW1's wind is so weak presents an interesting mystery.